Notes on the marine algae of the International Biosphere Reserve Seaflower, Caribbean Colombia IX: new records of Lobophora declerckii, Taonia abbottiana and Verosphacela ebrachia for Colombia - Y. Carla M. Daza; Paola Andrea Franco; Victor Díaz; Álvaro A. Sandoval; Brigitte Gavio (Acta Botanica Mexicana)
Background and Aims: During the Seaflower Scientific Expedition in 2019, extensive seaweed collection was carried out around Old Providence and Santa Catalina islands. Despite the intensive phycological studies realized during the past decade, new reports of macroalgae are still recorded for the Seaflower Biosphere Reserve. The objective of this work is to present three new records of brown algae for Colombia. Methods: The algal sampling was carried out in September 2019 during the Seaflower Scientific Expedition. The samples were collected around the Providencia and Santa Catalina islands in coral patches ecosystems, by SCUBA diving at depths between 3 and 16 m. The algae collected were preserved in a 4% formalin/seawater solution. The identification was carried out using optical and stereoscopic microscopes. All specimens were deposited in the herbarium JIW of the Biology Department of the Universidad Nacional de Colombia, Bogotá, Colombia. Key results: Three species of brown algae are newly reported for Colombia: Lobophora declerckii, Taonia abbottiana and Verosphacela ebrachia. Verosphacela has been reported, to date, only from the type locality in Florida and from Isla Mujeres, in Mexico. Due to its cryptic and small habit, it may be much more common than actually reported. Lobophora declerckii is apparently the most common species of Lobophora in the Archipelago. Taonia abbottiana may be much more common than reported to date, but it is easily confused with Stypopodium zonale. Conclusions: Despite the intense phycological research carried out in the past decade in the Archipelago of San Andrés, Old Providence and Santa Catalina, there is still much to be discovered.